Managing Public Finance and Procurement in Fragile and Conflicted Settings - Porter, Doug; Andrews, Matt; Turkewitz, Joel A.; Wescott, Clay (Taylor and Francis, 2013)
Successful transition from conflict and fragility hinges on the quality and legitimacy of public financial management (PFM) systems. This article shows that such systems develop asymmetrically in these settings. Formal aspects of modern systems are adopted, but a layered series of informal arrangements govern resource management. Analysis of data from Public Expenditure and Financial Accountability assessments of 101 countries explores aspects of this asymmetry and different explanations are considered for why elites seem to choose not to invest trust, resources, and capacity in making mainstream PFM systems functional. These explanations focus on the incentives created by three “public” resources: illicit flows, domestic revenues, and strategic or aid flows. Mainstream PFM systems are applied to a small part of these flows. The illustrative case of Cambodia shows how a layered system has emerged to govern such flows, undermining the influence of formal public finance management systems. The article offers suggestions to address these issues.